The incidence of esophageal cancer and dysplasia in a Chinese population with nondysplastic Barrett's esophagus - Lee, Shou‐Wu (JGH Open, 2018)
AIM: The aim of this study was to investigate the incidence of dysplastic transformation of Barrett's esophagus (BE) in a Chinese population. METHOD: Data from nondysplastic BE patients at Taichung Veterans General Hospital were collected from May 2008 to June 2017. The enrolled individuals received regular upper gastrointestinal (UGI) endoscopy during follow up. The pathological transformations, including low‐grade dysplasia (LGD), high‐grade dysplasia (HGD), or esophageal adenocarcinoma (EAC), were collected prospectively until June 2017. Rates of progression were calculated in cases with a diagnosis of dysplasia or EAC. RESULTS: There were 51 subjects who met the inclusion criteria, with a mean follow up of 3.71 years (SD, 1.61) and a total follow up of 189.1 patient‐years. Eight cases (15.7%) developed LGD, with a calculated incidence rate of 2.9% per year. The mean time to development of LGD was 3.26 years (SD, 2.68–3.84). One subject (2%) developed EAC, with a calculated incidence rate of 0.4% per year. No case with HGD was detected. CONCLUSION: In a Chinese population with nondysplastic BE, 15.7% of cases developed LGD, with an incidence rate of 2.9% per year, and 2% of cases developed EAC, with an incidence rate of 0.4% per year.